Employee Engagement and Competitiveness: Some Preliminary Analysis and Insights - Bozhinovska, Tihona (Slovenian Academy of Management [Društvo slovenska akademija za management], 2024)
Theoretical background and purpose of the study: Employee engagement is a construct that has been widely investigated from the organizational sciences perspective in the past few decades. Employee engagement is a contrast that incorporates the employees’ dedication and involvement in their job and in the fulfilment of the job-related roles. Numerous authors have attempted to define employee engagement and to elaborate all the concepts of the concept (Khan, 1990; Maslach and Later, 1997; Beker and Demerouti, 2007; Bailey, 2016). Additionally, significant number of studies focus on the investigation of the antecedents and the consequences of employee engagement mostly from the management perspective (such as: Saks, 2006; Saks, 2019; Robinson, 2007; Zeng et al., 2020, Govender and Busin, 2020; Aisa et al., 2023). However, dome of the research efforts in the past decade are highlighting the importance of employee engagement for introducing new concepts of human resource management and for enhancing the overall organizational performance (Saks, 2022; Gruman and Saks, 2011). Namely, Gruman and Saks (2011) elaborate the importance of employee engagement for overall organizational effectiveness and introduce the model of the form of performance management called the engagement management model. Although the relation between human resource management or to be more precise the strategic human resource management and competitiveness has been thoroughly investigated, there seems to exist a gap in the research regarding the relation of employee engagement with the overall national competitiveness and growth. However, recently some authors have analyzed the relation between human resource practices and competitiveness, relying on the endogenous growth theory assumptions (Sheran et al., 2013). Nonetheless, most of the studies on antecedents and consequences of employee engagement focus only on the organizational preconditions for increasing employee engagement and the organizational consequences. Considering the identified gap in the literature and the existing research on the association between human resource practices, on the one side, and employee engagement and innovation (Sheran et al., 2013) and competitiveness (Albrecht et al., 2015), on the other side, conducting research on the relationship between employee engagement on a country level and the variables related to the level of labor utilization and countries competitiveness should be considered. Methods: To investigate the relationship between employee engagement on national level and countries labor utilization and countries competitiveness, a correlation analysis was conducted. The data on employee engagement was gathered from the Gallup research on employee engagement by country in the period 2019-2022. Regarding the variables labor utilization, average hours worked per person employed and gross national income per hour worked (presented in USD, current prices) data from the OECD dataset were used. Regarding the countries competitiveness the rankings by the IMD World competitiveness center were used. In total data for 63 countries for the period between 2019 and 2022 were gathered. The total number of observations varied between 136 and 247. Findings: The results from the analysis indicate that the percentage of engaged employees is statistically significantly corelated with labor utilization, average hours worked per person employed, gross national product per hour worked and countries competitiveness ranking. The Pearson correlation between the percentage of engaged employees and labor utilization (hours worked per head of population) is statistically weaker (it is significant at the 0.05 level), while the other three correlations are statistically significant at level 0.01. Furthermore, Kendall's tau_b and Spearman's rho coefficients between the percentage of engaged employees, on the one hand, and labor utilization, average hours worked per person employed, GNP per hours worked and countries competitiveness ranking, on the other hand, are statistically significant at level 0.01. Limitations and further research: Although the correlations indicate the existence of certain associations between the analyzed variables, we must take into consideration the limitations of these methods. These findings only suggest the existence of certain associations that should be further investigated. In future research the analysis of the nature of the association between employee’s engagement and countries’ competitiveness (measured by countries’ ranking or by countries’ competitiveness index) should be deepened. Namely, future research should focus on investigating whether countries’ competitiveness can be analyzed as a predictor or as a consequence of employee engagement levels.
This a Book of Abstracts from the 7th International Conference on Management and Organization: MANAGING PARADOXES IN AND ACROSS ORGANIZATIONS, (organized in Belgrade, Serbia, June 20-21, 2024), edited by : Ana Aleksić Mirić, Matej Černe, Tomislav Hernaus, Amadeja Lamovšek, Maša Košak.
Keywords: employee engagement, competitiveness, labor utilization